Active monetary policy, passive fiscal policy and the value of public debt: some further monetarist arithmetic - Leopold von Thadden (Deutsche Bundesbank, 2003)
We consider the properties of two monetary policy rules ("strict inflation targeting", "constant money growth rule") in an intertemporal equilibrium model with flexible prices in which monetary policy is "active", while fiscal policy is "passive". Specifically, we assume that the fiscal agent takes the monetary policy rule as given and restricts itself to a policy which is consistent with a sustainable debt burden and stable steady-state dynamics. The paper shows that dynamic properties of the model economy may differ significantly between the two monetary policy rules if public debt is issued in nominal terms. Under a constant money growth rule which allows for temporary deviations of inflation from target in response to shocks there is scope for revaluations of public debt, acting as automatic stabilizers of government debt dynamics. By contrast, a policy of strict inflation targeting implements the target inflation rate also outside the steady state and precludes thereby such stabilizing revaluations. Owing to this feature, additional fiscal restraint may be needed which is not required under a constant money growth rule. – – Diese Arbeit untersucht die Eigenschaften zwei verschiedener geldpolitischer Regeln (strikte Inflationssteuerung, konstante Geldmengenzuwachsrate) in einem intertemporalen Gleichgewichtsmodell mit flexiblen Preisen unter der Annahme einer 'aktiven' Geldpolitik und einer 'passiven' Fiskalpolitik. Insbesondere wird davon ausgegangen, dass der Fiskalagent die geldpolitische Regel als gegeben betrachtet und sich auf eine Politik beschränkt, die mit einer tragfähigen Schuldenbelastung und einer stabilen Steady-State Dynamik vereinbar ist. Die Arbeit zeigt, dass sich für die beiden geldpolitischen Regeln die dynamischen Eigenschaften der Modellökonomie signifikant unterscheiden können, wenn die Staatsschuld nominal begeben wird. Die Regel einer konstanten Geldmengenzuwachsrate läßt außerhalb des Steady-State Gleichgewichtes vorübergehende Abweichungen der Inflationsrate vom Inflationsziel zu und ermöglicht dadurch Umbewertungen der Staatsschuld, die stabilisierend auf die staatliche Schuldendynamik wirken. Demgegenüber implementiert eine Politik einer strikten Inflationssteuerung die Zielinflationsrate auch außerhalb des Steady-State Gleichgewichtes und verhindert dadurch stabilisierende Umbewertungen der Staatsschuld. Diese Eigenschaft führt dazu, dass der Fiskalagent zusätzlichen Beschränkungen unterworfen sein kann, die bei einer Politik einer konstanten Geldmengenzuwachsrate nicht auftreten.
Keywords: H62; E52; E63; 330; Monetary policy; Fiscal regimes; Overlapping generations; Geldpolitik; Inflation Targeting; Geldmengensteuerung; Finanzpolitik; Steady-State-Wachstum; Overlapping Generations; Intertemporales Gleichgewicht; Öffentliche Schulden; Theorie